Ethical Concerns and Psychophysical Impacts of Artificial Intelligence: A Study through the Lens of the Theory of Planned Behavior among Youth and Adults - Ruby Sharma (Journal of Informatics Education and Research, 2025)
The rapid advancement and integration of artificial intelligence (AI) into everyday life have generated profound psychophysical and ethical challenges, particularly among youth and adults. This study explores these challenges by investigating ethical concerns and psychophysical modifications associated with frequent AI use, adopting the Theory of Planned Behavior (TPB) as the guiding framework. A quantitative research design was employed to examine constructs including emotional dependency, attention span, cognitive strain, behavioral intention, and ethical awareness. Data were collected from 120 participants (60 youth and 60 adults) using validated instruments such as the AI Exposure Scale (AES) and the Ethical Awareness Inventory (EAI). Statistical analyses, including t-tests and multiple regression, revealed significant age-based differences. Youth participants exhibited greater emotional reliance on AI technologies and shorter attention spans, whereas adults demonstrated heightened ethical sensitivity and awareness. These findings highlight the generational variations in AI’s influence and underscore the urgent need for targeted interventions in digital literacy and ethical AI education, with particular emphasis on younger populations. By situating the discussion within TPB, the study provides valuable insights into the interplay between attitudes, perceived control, and intentions in shaping responsible AI usage.